The global state, trajectory and trends of bacterial extracellular vesicles: a bibliometric and visualized analysis - Chen, Haokai; Xie, Qiyu; Cai, Jiayu; Xin, Qing; Yao, Wei; Xu, Hong; Zhou, Zongke (Frontiers in Microbiology, 2025)
IntroductionBacterial extracellular vesicles (BEVs) are nanoscale biological vesicles secreted by bacteria that carry unique cargo and membrane structures derived from their parental bacteria. In recent years, BEVs have been shown to significantly contribute to the pathogenesis and progression of various diseases, with promising potential as immunotherapeutic agents, drug delivery systems, and nano-vaccines.MethodsThis study aims to comprehensively evaluate the research status and development trends of BEVs using bibliometric approaches. A total of 2,836 publications indexed in the Web of Science Core Collection by 30 November 2024 were included in this study. The R package “Bibliometric” and CiteSpace software were employed for bibliometric analysis and visualization of authors, countries/regions, institutions, journals, subject categories, keywords, and references.ResultsFrom 2006 to 2024, the number of publications exhibited a steady upward trend, with an annual growth rate of 15.01%. The USA and the Chinese Academy of Sciences were identified as the most productive country and institution, respectively. Gho, Yong Song emerged as the most prolific and influential researcher. Cluster analysis of references revealed that outer membrane vesicles, immunotherapy and probiotics are the three largest research clusters. Keyword burst detection identified cancer immunotherapy, the tumor microenvironment, and drug delivery as promising research directions.ConclusionOur study highlights that BEV-based drug delivery systems are a major focus of current research, with tremendous potential. Future research on BEVs is expected to focus on tumor immunotherapies and remodeling of the tumor immune microenvironment. With the advancements in nanotechnology, biomedicine, and industry, BEVs are anticipated to make remarkable strides and greatly contribute to solving challenging clinical issues.